1994
DOI: 10.1080/07399339409516126
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward surrogate motherhood in Canada

Abstract: The issue of surrogate motherhood captured worldwide attention with the Baby M case in the United States. Some medical practitioners now claim that the surrogate arrangement may be the answer for certain women who are unable to conceive children naturally. Feminist activists are highly critical about the issue. In her landmark book The Mother Machine, Corea (1985) called surrogates "breeders," women whose bodies are being used by men. Lawyers and ethicists debate whether surrogacy is baby selling or not, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
12
0
6
Order By: Relevance
“…Demographic differences in approval rates appear quite minimal. In Krishnan's (1994) analysis of data from a Canadian national fertility survey of over 5,000 women in the childbearing years, size of family of origin, age, and religiosity were negatively associated with approval of commercial surrogacy whereas education was positively associated. Together, however, these and other demographic variables explained only seven percent of the variance in attitudes toward commercial surrogacy.…”
Section: Attitudes About Surrogacymentioning
confidence: 94%
See 1 more Smart Citation
“…Demographic differences in approval rates appear quite minimal. In Krishnan's (1994) analysis of data from a Canadian national fertility survey of over 5,000 women in the childbearing years, size of family of origin, age, and religiosity were negatively associated with approval of commercial surrogacy whereas education was positively associated. Together, however, these and other demographic variables explained only seven percent of the variance in attitudes toward commercial surrogacy.…”
Section: Attitudes About Surrogacymentioning
confidence: 94%
“…A reproductive technology will be used only if it is considered acceptable by potential consumers. Studies to date support the assertion that contractual parenting, especially when it involves a financial payment to the birth mother for carrying a child, is perceived as the least acceptable of all assisted reproductive technologies, with approval percentages ranging from below 10% to about 25% in surveys of college students (Dunn, Ryan, & O'Brien, 1988; Lasker & Borg, 1994), Psychology Today readers (cited in Lasker & Borg, 1994, p. 168), Canadian women of child‐bearing age (Krishnan, 1994), and infertile women in Great Britain (van den Akker, 2001). This is a much lower percentage than people who approve of or state that they might consider IVF, embryo transplant, and AI by husband (Dunn et al, 1988).…”
Section: Attitudes About Surrogacymentioning
confidence: 99%
“…Research on attitudes towards surrogacy, at the same time period as many media reports were also largely negative throughout the 1980's, 90's and well into the millennium (Dunn et al, 1988;Appleton, 1990;Bromham, 1991;Halman et al, 1992;Genius et al, 1993;Krishnan, 1994;Frazier and Chapman, 1994;BMA, 1996;Chliaoutakis et al, 2002;Suzuki et al, 2006;Poote and van den Akker, 2009), although other recent surveys report more variable attitudes (Dempsey and Critchley, 2010;Constantinidis and Cook, 2012). This demonstrates a general discord between the practice of surrogacy and the populations' perception of it, and a simultaneous alarmist framed media portrayal of British altruistic surrogacy.…”
Section: Discussionmentioning
confidence: 99%
“…Surrogacy does not conform to traditional family building norms even in societies where social variations in family formation are increasingly common (van den Akker, 2007). Attitude surveys have demonstrated that surrogacy is the least acceptable method of family building (Dunn et al, 1988;Halman et al, 1992;Genius et al, 1993); non-commercial altruistic surrogacy is more acceptable than commercial surrogacy (Krishnan, 1994), and religion affects acceptability of surrogacy (Chliaoutakis et al, 2002;Dempsey and Critchley, 2010). Partial surrogacy is also perceived as less acceptable than full surrogacy (Appleton, 1990;Bromham, 1991;Frazier and Chapman, 1994;BMA, 1996;Suzuki et al, 2006;Poote and van den Akker, 2009), although more recent research has shown attitudes to be more variable (Dempsey and Critchley, 2010;Constantinidis and Cook, 2012).…”
mentioning
confidence: 99%
“…2008;Kovacs et al, 2003;Lasker and Murray, 2001;Suzuki et al, 2011). If focusing on surveys on commercial surrogacy, an increase in negative attitudes is 4 reasonable to expect (Krishnan, 1994). Among scholars, an equally strong resistance against surrogacy and in particular its commercial version is common.…”
Section: Surrogacy and The Harm Argumentmentioning
confidence: 99%